Printed Copper Nanoparticle Metal Grids for Cost‐Effective ITO‐Free Solution Processed Solar Cells - Georgiou, Efthymios; Choulis, Stelios A.; Hermerschmidt, Felix; Pozov, Sergey; Burgués-Ceballos, Ignasi; Christodoulou, Constantinos; Schider, Gerburg; Kreissl, Stefanie; Ward, Richard; List-Kratochvil, Emil J. W.; Boeffel, Christine (My University, 2018)
Copper nanoparticle inks have drawn much attention since they have the potential to constitute an alternative cost-effective solution than other noble metals nanoparticle inks such as Ag for indium tin oxide (ITO)-free printed electronic applications. Our research and development efforts have produced high conductivity copper nanoparticle inks which have excellent jetting and printing properties resulting in high quality inkjet-printed (IJP) Cu nanoparticle-based metal grids. We present ITO-free, Si-PCPDTBT: PC[70]BM organic photovoltaics (OPVs) processed in ambient low-cost fabrication conditions comprising for the first time embedded and non embedded inkjet-printed copper grid/Poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) as the bottom electrode with power conversion efficiencies (PCE) of 2.56 and 3.35%, respectively. The results of the ITO-free OPVs using inkjet-printed Cu nanoparticle current collecting grids are discussed relevant to reference ITO-based OPVs with PCE of 4.92%.
Keywords: Copper-based flexible electronics; Copper electrodes; Copper nanoparticle inks; Inkjet-printed; ITO-free organic photovoltaics; Printed electronics; Solution processed solar cells